KEANEKARAGAMAN MAKROFAUNA TANAH PADA BERBAGAI TIPE TEGAKAN DI AREAL BEKAS TAMBANG SILIKA DI HOLCIM EDUCATIONAL FOREST, SUKABUMI, JAWA BARAT Soil Macrofauna Diversity on Various Types of Stands in Silicas’ Post-Mining Land in Holcim Educational Forest... - Cahyo Wibowo; Syamsudin Ahmad Slamet (Jurnal Silvikultur Tropika, 2017)
Soil Macrofauna has a very important role in maintaining soil fertility through the decomposition of organic matter, nutrient distribution, increasing soil aeration and so on. The existence of soil macrofauna are very important in helping the process of rehabilitation of post-mining land because they contribute to the improvement of the physical, chemical, and biological properties of soil. The purposes of this study are to identify and quantify the diversity of soil macrofauna in various types of stands and land without stand in Holcim Educational Forest. The highest abundance of soil macrofauna was found in mixed stand with 240 individuals in nine plots of observation, each plot was 40 cm x 40 cm. Layers of soil (0-10 cm) has an abundance of soil macrofauna higher than in the litter layer, because soil layer can provide protection from direct sunlight and enough food for soil macrofauna. Mixed stand has the highest soil macrofauna diversity (H '= 2.52, DMG = 6.93, J' = 0.63), as it has a more diverse vegetation and highest canopy density. Environmental conditions such as soil temperature, canopy density, and soil organic matter can influence the composition and abundance of soil macrofauna, so that the soil macrofauna can be used as an indicator in monitoring environmental quality. Soil macrofauna that dominates in all the stands and land without stand, were red ants (Formicidae 7), termites (Rhinotermitidae 1), earthworms (Megascolecidae 1), and larvae of Coleoptera (Scarabaeidae 1).Key words: abundance, diversity, environment, soil macrofauna